EDUKASI ECOPRINT DAN DAUR ULANG BOTOL BEKAS MENJADI CELENGAN SEBAGAI PRODUK KREATIF BERNILAI EKONOMI DI DESA TEWANG PANJANG KABUPATEN KATINGAN - Firlianty Firlianty; Ellydia Ludang (Bajang Institute, 2025)
Plastic waste, particularly single-use plastic bottles, has become a growing environmental issue in both urban and rural areas. Tewang Panjang Village, Katingan Regency, faces similar challenges due to limited waste management systems and low utilization of plastic waste into economically valuable products. Conversely, the village possesses abundant natural resources that can be utilized for environmentally friendly creative economic development. This community service program aimed to enhance environmental awareness and creative economic skills through ecoprint education and the recycling of plastic bottles into piggy banks with economic value. The program employed a participatory community empowerment approach, including preparation, socialization, and hands-on practice. The results indicated increased community knowledge and skills, the creation of ecoprint products and recycled piggy banks, as well as improved environmental awareness and entrepreneurial motivation. This program contributes to strengthening local creative economy and supporting sustainable environmental management in Tewang Panjang Village